Musykilātu Tarjamati Al-Nushus Al-‘Arabiyati wa Mu’ālajatuha - hamdan; Musa; Firdaus, Muhammad (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2023)
This study discusses the problems faced by Islamic Boarding School students of Al-Azhar Pegasing Takengon in Arabic script translation skills. The problem is how to transfer speech from the source language to the target language without changing the original meaning and therefore it can be understood by the readers of the target language properly and correctly. Consequently, there is a need for a communicative translation theory, namely a theory that departs from understanding the writing and language aspects of the target language reader. The research method employed in this article is a descriptive approach, while the method of collecting data and research information uses two methods, including library research methods and field research methods. The problems faced by students in learning translation are: (1) weak vocabulary understanding, (2) weakness in understanding morphology and syntax rules, (3) weakness in understanding the use of verb changes, (4) lack of repetition of Arabic text material independently , (5) Difficulty in constructing Indonesian sentences, (6) poor ability to distinguish between idhafah and conjunctions. Several solutions are offered which include students developing motivation to learn translation because translation is one of the important lessons in our religion (understanding Islamic and Sharia law), and they must enrich themselves with a wealth of language rules so that they can easily translate texts. Arabic text and they should learn the translation well.